2021
DOI: 10.17352/2455-5487.000088
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of neck pain among the undergraduate physical therapy students of university of Balochistan, Quetta, Pakistan

Abstract: Objective: To assess the prevalence of pain among the undergraduate physical therapy students of university of Balochistan, Quetta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…8,24,25 The prevalence of neck pain among undergraduate students in this study is higher than countries, such as Ethiopia (49.2%), 26 India (46.9%), 27 Singapore (74%) 28 and Taiwan (52%) 29 and lower than a study conducted in China (72.9%). 30 However, the findings is in accord with a study conducted in Brazil (66.7%), 31 Pakistan (69%) 32 and Malaysia (65.1%). The observed variability in the prevalence rate of NP across studies could be attributed to disparities in multiple factors, including the geographical setting of the study, the size of the sample population, the methodology employed for sampling, and the assessment instruments utilized.…”
Section: Discussionsupporting
confidence: 70%
“…8,24,25 The prevalence of neck pain among undergraduate students in this study is higher than countries, such as Ethiopia (49.2%), 26 India (46.9%), 27 Singapore (74%) 28 and Taiwan (52%) 29 and lower than a study conducted in China (72.9%). 30 However, the findings is in accord with a study conducted in Brazil (66.7%), 31 Pakistan (69%) 32 and Malaysia (65.1%). The observed variability in the prevalence rate of NP across studies could be attributed to disparities in multiple factors, including the geographical setting of the study, the size of the sample population, the methodology employed for sampling, and the assessment instruments utilized.…”
Section: Discussionsupporting
confidence: 70%
“…In the present study, smartphone usage of ≥nine h per day was associated with ≥one positive clinical myelopathic sign, with an adjusted odds ratio of 1.85 (95% CI = 1.05 to 3.26). Previous studies have found that smartphone use leads to musculoskeletal problems, particularly in the neck region [3][4][5], and that the neck is most affected when using smartphones in the sitting posture [5,26,37]. In our study, approximately 42% of the participants reported using their smartphones in a sitting position.…”
Section: Discussionmentioning
confidence: 47%
“…26 A national study among undergraduate physical therapy students of the University of Balochistan, Pakistan concluded that the prevalence of neck pain among mobile users was 69%. 27 Also a local study conducted among undergraduate students of two universities in Lahore showed that 56.7% of students were having neck pain for the same reason. 28 Additionally, our research included 244 students (91.7%) who began using smartphones between the ages of 11 and 20, primarily by personal choice.…”
Section: Discussionmentioning
confidence: 99%